Identity, cooperation, and punishment - Kendra N. McLeish; Robert J. Oxoby (Institute for the Study of Labor (IZA), 2007)
Among economists, there is increased recognition of the role individuals' identities play in decision-making. In this paper, we conduct laboratory experiments in which we explore the motivations for and the effects of group identity. We find that negative out-group opinion (acting as an inter-group identity threat) can motivate in-group/out-group effects in a simple bargaining context. Further, our results suggest that disparagement of group norms by members of the in-group (acting as an intra-group identity threat) increases the use of costly punishment within the in-group
urn:nbn:de:101:1-20080425231
Keywords: 330; Gruppenentscheidung; Persönlichkeitspsychologie; Gerechtigkeit; Kooperatives Spiel; Test